Influence of Dardanelles outflow induced thermal fronts and winds on drifter trajectories in the Aegean Sea - GERIN, R.; KOURAFALOU, V.; POULAIN, P.-M.; BESIKTEPE, Ş. (Mediterranean Marine Science, 2014)
The data provided by 12 drifters deployed in the Northern Aegean Sea in the vicinity of the Dardanelles Strait in August 2008 and February 2009 are used to explore the surface circulation of the basin and the connectivity to the Black Sea. The drifters were deployed within the Dardanelles outflow of waters of Black Sea origin in the Northeastern Aegean. Thanks to the particular choice of the drifter deployment positions, the data set provides a unique opportunity to observe the branching behaviour of the surface currents around Lemnos Island. Such pathways were not possible to study with previous drifter deployments that were far from the Dardanelles Strait. In addition, the drifter tracks covered the Aegean basin quite thoroughly, mapping major circulation features and supporting the overall general circulation patterns described by previous observational and modelling studies. The collected data display cases in which drifters are driven by winds and thermal fronts. Wind products were used to estimate the influence of the atmospheric forcing on the drifter trajectories. Satellite sea surface temperature images were connected to the drifter tracks, demonstrating a high correlation between the remote and in situ observations. The waters of Black Sea origin were traced all the way to the Southern Aegean, establishing a strong connectivity link between the Aegean and Black Sea basins.